2009
DOI: 10.1002/jmor.10820
|View full text |Cite
|
Sign up to set email alerts
|

Topography of the chorda tympani nerve and the tensor tympani muscle in carnivores provides a new synapomorphy for Herpestidae (Carnivora, Mammalia)

Abstract: The topographical relationship of the chorda tympani nerve (chorda tympani) to the tensor tympani muscle in the middle ear of carnivores provides new phylogenetic information. The examination of histological serial sections of 16 carnivore species representing most families revealed two distinct character states concerning the course of the chorda tympani: a hypotensoric state with the nerve running below the insertion tendon of the tensor tympani muscle, and an epitensoric state with the nerve running above t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Regarding the course of the chorda tympani, there are two different patterns in general: a hypotensoric pattern with the nerve running below the insertion tendon of the tensor tympani muscle, and an epitensoric pattern with the nerve running above the tendon [20]. In almost all mammals the chorda tympani passes underneath the tendinous insertion of the tensor tympani muscle at the malleus [11,16,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the course of the chorda tympani, there are two different patterns in general: a hypotensoric pattern with the nerve running below the insertion tendon of the tensor tympani muscle, and an epitensoric pattern with the nerve running above the tendon [20]. In almost all mammals the chorda tympani passes underneath the tendinous insertion of the tensor tympani muscle at the malleus [11,16,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, in some rodents and primates, the course of the chorda tympani shows a derived condition [9,11,16,19]. To resolve problems of phylogenetic systematic of carnivores, some authors have investigated the middle ear of different species of carnivores only histologically [1,16,19,20]. In accordance with these studies, the canids, ursids, phocids, ailurids, mustelids, felids, nandiniids, euplerids, and viverrids showed the hypotensoric state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruf et al (2009) demonstrated that in the order Rodentia the epitensoric chorda was realized six or seven times independently; however, this apomorphic state is almost always found in monophyletic subgroups of rodents thus lending further support to their validity. Finally, Ruf and Maier (2010) could show that within the carnivores the epitensoric state is bound to the family Herpestidae only. Bondy (1907) studied the middle ears of about 50 mammalian species covering almost all major taxonomic units.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies confirmed the notion of Bondy (1907) that the overwhelming number of mammal species have retained the hypotensoric situation, whereas the epitensoric state had been acquired only by a few well defined taxonomic groups. For instance, in carnivores, Ruf and Maier (2010) demonstrated that the epitensoric chorda occurs only in the family Herpestidae, thus confirming them as a monophyletic unit. Ruf et al (2009) studied a great number of rodents by means of histological serial sections and found the apomorphic state only in seven monophyletic groups: Aplodontidae, Gliridae, Castoridae, Ctenodactylidae, Anomaluridae, and Pedetidae; it is also found in the Sciuridae, but this is the only family for which we have good evidence that epitensoric conditions developed within the group (Fig.…”
mentioning
confidence: 95%